Evolução no período de 20 anos dos parques públicos municipais da cidade de São Paulo: uma análise da distribuição territorial - Gadelha, Juliana Peixoto de Novais (2021)
Given the context of the urbanization process in the city of São Paulo, which occurred in an accelerated and disordered manner, areas of urban and social vulnerability originated, compromising the environment and the quality of life. The public park is an urban instrument, providing environmental services and may contain spaces and equipment for leisure. The present work has as generais objective to analyze if the parks are distributed equally in the territory of the city of São Paulo and the evolution in its implementation process and as a specific objective it was considered to analyze if the parks are accessible through the structural network of urban mobility and the spaces and equipment for leisure inserted in the parks. For this, a theoretical basis was built, seeking the construction of knowledge, the Case Study method was used, with an exploratory objective and a qualitative approach. Finally, answering the question proposed in the research: “How are the public parks in the city of São Paulo distributed in the territory and evolving over the period of 20 years?”, A triangulation was carried out: case data, normative acts and the theoretical framework, it is concluded that the evolution of the parks became contextualized with the development of the city and the normative acts converged to the evolution, the parks are not distributed in the territory in an equitable way and there are parks that have greater difficulty of access, mainly those located at the ends of the zones and aiming at the leisure that the parks provide, playground equipment stood out with a greater%. The research may contribute to urban planning.